Increasing water and wastewater utility participation in demand response programs - Robert B. Sowby (Elsevier, 2021)
The reliance of water utilities on the electric grid, and their ability to buffer its peak demands, are important components of the energy–water nexus. Demand response (DR) among water and wastewater utilities is an underutilized resource for balancing electric loads and is increasingly important as the energy industry transitions to cleaner but intermittent renewables. Challenges to greater participation include water operators’ risk aversion, DR research that misses water sector stakeholders, the hourly and seasonal variability of water demand, the intricacies of power rate schedules, and a lack of convincing data on payback. Actions by particular groups can help overcome these challenges. Power utilities should acknowledge water operators’ risk preferences, work with them to develop site-specific DR practices, and educate them on rate schedules and DR necessity. Water utilities should learn about their power bills and share information about their water operations that will help power companies assess DR potential. DR researchers should consider water operators’ risk perceptions, explore ways to work around hourly flow variations, involve water sector co-authors in their work, develop DR case studies with cost-benefit analyses, and share their research with water sector audiences. These actions will help increase DR penetration in the water sector.